THE ISSUE OF CORRELATION BETWEEN ABSOLUTE AND RELATIVE HUMAN RIGHTS: LOGICAL-GNOSIOLOGICAL ANALYSIS - Паранюк, Дан; Melenko, Serhiy (Lumen Publishing House, 2018)
Due to applying the newest methodological techniques in performing a profound scientific logical-gnoseological analysis, the article under discussion reveals certain axiological factors, which might be regarded as ontological “markers” of such indispensable human rights as the right to life and the right to personal inviolability. In order to achieve the goal, set by the authors of the article, they have carried out a profound juridical-philological analysis of the contents of the articles of the II and III European Conventions on of Human Rights of 1950. While analyzing the juridical contents of numerous cases, heard by the European Court of Human Rights on the protection of the right to life and the right to personal inviolability, the authors of the article have reached somewhat ambiguous conclusions. The latter may serve as an efficient ground for further research in the field of logical-gnosiological analysis of the human rights protection, ensured by the European Convention on Human Rights of 1950. In particular, the article under studies reasonably questions the unambiguous perception of the individual’s right to personal inviolability as something absolute and indisputable. This critique has been stipulated by a profound logical-ontological analysis of the court file of the lawsuit “Gäfgen v. Germany”, which was heard by the European Court of Human Rights. In addition, the authors of the article have certain doubts concerning the fact that the individual’s right to life has been referred to as a relative one. The above doubts have resulted from a profound logical juridical-philological analysis of the lawsuit court file “McCann and Others v. United Kingdom”. Another thing that causes the whole range of questions, is the correlation between the axiological components of the protection of the individual’s right to life and his/her personal inviolability. In other words, why is the right to life is referred to the list of relative human rights, whereas individual’s personal inviolability – to that of absolute ones? The authors of the article do not expect that their investigation will somehow mitigate the importance of the issue of correlation between the right to individual’s personal inviolability and his/her right to life. Consequently, they are open for further scientific discussions on the subject both during the conference and on the pages of various scholastic journal.
Keywords: human rights; the European Convention on Human Rights; the right to life; the right to personal inviolability; the European Court of Human Rights; the prohibition of tortures